Outcome of ondansetron on subarachnoid block-induced hypotension in infraumbilical surgeries - Renganathan S; Navin C; Ganesh Prabhu SC (Asian Journal of Medical Sciences, 2025)
Background: Bradycardia and hypotension are common post-subarachnoid block (SAB) complications that can result in adverse outcomes. The 5-HT3 receptor antagonist ondansetron, which is often used as an antiemetic, has recently been studied for its possible effect on preserving hemodynamic stability during SAB. Aims and Objectives: This study aimed to assess the effect of prophylactic intravenous (IV) ondansetron administration on the incidence of SAB-induced hypotension and bradycardia in patients undergoing infraumbilical surgery. Materials and Methods: This prospective, randomized, controlled study included 100 patients undergoing infraumbilical surgery under spinal anesthesia. Patients were randomly divided into two groups: control (placebo, n=50) and ondansetron (8 mg IV, n=50). Systolic blood pressure, mean arterial pressure (MAP), and heart rate were the hemodynamic parameters measured at baseline and 5, 10, 15, 20, and 30 min after SAB. The incidence of hypotension and the need for vasopressors were the primary outcomes. The prevalence of bradycardia and atropine use was secondary outcomes. Results: The incidence of SAB-induced hypotension was significantly lower in the ondansetron group (14%) than in the control group (44%) (P=0.001). Ephedrine use was also significantly lower in the ondansetron group (14% vs. 44%, P=0.001). MAP remained significantly higher in the ondansetron group at 10-, 15-, 20-, and 30-min post-SAB (P<0.05). The incidence of bradycardia was not significantly different between the groups (P=0.559). Conclusion: Prophylactic ondansetron administration significantly decreased the incidence of SAB-induced hypotension and the need for vasopressors. Ondansetron may contribute to improved hemodynamic stability during spinal anesthesia, thereby lowering the risk of related complications.